Lepus (Poecilolagus) americanus Erxleben 1777 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lepus (Poecilolagus) americanus Erxleben 1777 Lepus (Poecilolagus) americanus Erxleben 1777, Systema Regni Animalis, Vol. 1: 330. Type Locality: "in America boreeli, ad fretum Hudsonis copiosissimus." Restricted by Nelson (1909:87) to Fort Severn, Ontario, Canada. Vernacular Names: Snowshoe Hare. Subspecies:: Subspecies Lepus (Poecilolagus) americanus subsp. americanus Erxleben 1777 Subspecies Lepus (Poecilolagus) americanus subsp. bairdii Hayden 1869 Subspecies Lepus (Poecilolagus) americanus subsp. cascadensis Nelson 1907 Subspecies Lepus (Poecilolagus) americanus subsp. dalli Merriam 1900 Subspecies Lepus (Poecilolagus) americanus subsp. struthopus Bangs 1898 Subspecies Lepus (Poecilolagus) americanus subsp. virginianus Harlan 1825 Distribution: S and C Alaska (USA) to S and C coasts of Hudson Bay to Newfoundland and Anacosti Isl (introduced) (Canada), south to S Appalachians, S Michigan, North Dakota, NC New Mexico, SC Utah, and EC California (USA). Conservation: IUCN – Lower Risk (lc). Discussion: Subgenus Poecilolagus (Gureev, 1964; Averianov, 1998). Distinctive small species, but subgeneric separation not supported Hall (1981:314). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Lagomorpha, pp. 185-211 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 195, DOI: 10.5281/zenodo.7316519